Mobile Banking Application Challenges and Continued Usage in Nigeria: Mediating Influence of Information and Systems Success Model - Amahi, Fidelis, U.; Ugbah, Andrew Azuka; Alajekwu, Udoka Bernard; Onuorah, Anastasia Chichi; Erhijakpor, Andrew. O.E.; Adegbite, Yetunde Abie (Journal of Posthumanism, 2025)
Although Nigerian banking industry has recorded tremendous growth in the volumes of mobile banking transactions, the extent of deployment of the mobile banking application (MBA) in Nigeria on the overall, is still below expectations. Consequently, this research investigated the influence of MBA technical (poor network connectivity - PNC, app compatibility issues - ACI, technical glitches - TEG, and frequent system failures - FSF) and user-related challenges (low digital literacy - LDL and Inadequate Customer Support - ICS) on continued usage (COU) of MBA in Nigeria leveraging on information quality (IFQ), system quality (SYQ), and service quality (SEQ). 387 web-based copies of questionnaire were sent to bank experts using Google forms. The data collected from the students were coded, and analysed using the SmartPls. The findings revealed that both user-related such as LDL and technical challenges such as PNC, ACI, FSF and CST significantly hinder COU while user-related such as TEG and ICS had insignificant direct influence on COU. However, the introduction of IFQ, SYQ, and SEQ into the model significantly enhances the robustness of the analysis by evidencing the relevant mediating mechanisms, which improves COU. Hence, the study concludes that PNC, ACI, FSF and CST can still improve COU indirectly when the quality dimensions (IFQ, SYG, and SEQ) are high. Policy-wise, the Central Bank of Nigeria (CBN) and other financial regulators should mandate banks on national awareness campaigns on the usage of MBA.